Implementation of Character Education in the Independent Curriculum - Idham; Rokimin; Muchammad Ibnu Muzakir (Universitas Darunnajah Jakarta, Indonesia, 2024)
This study analyzes the importance of character education within the framework of the independent curriculum, focusing on the integration of moral values in learning, the role of school leadership, and collaboration between teachers, parents, and the community. The method in this study uses a descriptive qualitative approach through literature studies from journals, books, and official documents. The results of the study show that the independent curriculum supports project-based learning, the flexibility of a holistic approach, and the role of transformational leadership in creating a school culture that supports character education. The challenges faced include limited teacher training, gaps in student backgrounds, and lack of program evaluation. The implication is the need to increase teacher training, strengthen the role of school principals, and integrate local values and digital technology to strengthen the effectiveness of character education. This research provides strategic recommendations for policymakers and educators in building a generation with character in the modern era